In Silico and In Vitro Inhibitory Activity of Indonesian Herbal Compound Extracts against SARS-COV-2 Recombinant Papain-Like Protease - Fatiningtyas, Fairuz Andini; Napitupulu, Riswanto; Malik, Amarila; Helianti, Is (HAYATI Journal of Biosciences, 2025)
The SARS-CoV-2 papain-like protease (PLpro) is essential for viral replication and a promising target for drug discovery. This study explored the inhibitory potential of compounds from Indonesia herbals Butterfly pea flower (Clitoria ternatea L), Star fruit leaves (Averrhoa carambola L.), and Java plum leaves (Syzygium cumini (L.) Skeels) against PL pro through molecular docking and in vitro assays. The molecular docking method utilized the target protein PLpro (PDB ID: 7CMD), with the native ligand obtained from compounds identified in these plant extracts. The compounds were identified using the KNApSAcK database and analyzed for drug-likeness based on Lipinski's Rule of Five. The physicochemical characteristics affecting absorption, distribution, metabolism, excretion, and toxicity (ADMET) were determined using the pkCSM descriptor algorithm protocol. Validation was performed using the redocking method, achieving an RMSD score of 0.728 Å, which indicated validity (RMSD <2.0 Å). The results identified four ligands with the lowest binding affinities from these extracts: (-)-Epicatechin 3-O-gallate, folic acid, petunidin 3-glucoside, and ellagic acid, with binding scores of -8.6, -8.3, -7.1, and -7.1 kcal/mol, respectively. Prior to conducting the PLpro in vitro inhibition assay, a fluorescence-based inhibition assay was performed using Z-RLRGG-AMC as the substrate and GRL0617as the control inhibitor. All extracts were subjected to 70% ethanol maceration. The IC50 value of GRL0617 was 3.38 μM, while fluorescence tests showed that Java plum leaf extract exhibited the highest inhibition percentage at 66.10±3.22%. These findings indicate that all three plant extracts contain compounds capable of inhibiting PLpro activity.